Measurement of the CP-violating phase ϕs in the Bs0→J/ψϕ(1020)→μ+μ−K+K− channel in proton-proton collisions at √s=13TeV; Physics Letters B; Vol. 816 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen